Availability of physical environments and incentives for physical activity in industry companies, Pelotas, Brazil - Virgílio Ramires; Airton Rombaldi; Grégore Mielke; Marlos Domingues; Pedro Hallal (Revista Brasileira de Atividade Física e Saúde)
Evidence shows that physically active individuals have lower risk of developing chronic diseases. Despite that, the rate of physical inactivity is high. Difficult access and lack of time are mostly reported as barriers to engaging in physical activity. The workplace is a key setting for physical activity promotion among employees. This study aimed to describe the physical environments and incentives for non-occupational physical activities offered to employees of local industry companies in the city of Pelotas, southern Brazil. A cross-sectional study was conducted with a sample drawn from the Pelotas Center for Businesses (CIPEL) and the Brazilian Special Guides Publisher (EBGE) databases. Companies with more than 20 employees were eligible to participate in the study. The final sample consisted of 81 companies and information was collected through a questionnaire applied to the participating company’s business representative. It was found that 12.4% of the companies had physical environments for physical activity at the workplace, 9.9% had spaces for indoor sports, 91.4% had showering facilities and locker rooms, 12.4% offered health club discounts and 16.0% subsidized memberships to health clubs and gyms. Participation in employee team sports was reported in 37.0% of the companies; it was the most common physical activity especially among male employees. In conclusion, local Pelotas companies did not offer their employees adequate spaces for non-occupational physical activity. However, the availability of physical environments such as showering facilities and locker rooms opens up great opportunities for active commuting to work.